Rendering multilingualism through audio subtitles: shaping a categorisation for aural strategies. Issue 4 (1st October 2020) - Iturregui-Gallardo, Gonzalo
ABSTRACT: Multilingualism in films has increased in recent productions as a reflection of today's globalised word. Different translation transfer modes such as dubbing or subtitling are combined to maintain the film's multilingual essence when translated into other languages. Within media accessibility, audio subtitles, an aurally-rendered version of written subtitles, is used to make access possible for audiences with vision or reading difficulties. By taking Sternberg's representation of polylingualism (1981. Polylingualism as reality and translation as mimesis. Poetics Today, 2(4), 221–239), this article offers a categorisation of the strategies that may be used to reveal multilingualism in audiovisual content through audio subtitles similar to the way Szarkowska, Zbikowska, & Krejtz (2013. Subtitling for the deaf and hard of hearing in multilingual films. International Journal of Multilingualism, 10(3), 292–312. Did with subtitles for the deaf and the hard of hearing. By taking a descriptive approach, two main strategies or effects for the delivery of audio subtitles – dubbing and voice-over – are highlighted and explained. By combining these two effects with the information provided by the audio description, the levels of the categorisation are defined from more to less multilingualism-revealing: vehicular matching, selective reproduction, verbal transposition, explicit attribution and homogenising convention.